Efeito gastroprotetor da goma guar (cyamopsis tetragonolobus) e galactomanana da fava danta (dimorphandra gardneriana) na gastrite experimental induzida por álcool - Pinto, Antonione Santos Bezerra (2019)
Gastrointestinal pathologies caused by abusive use of alcohol lead to an inflammatory reaction, which in turn results in lesions such as gastritis and peptic ulcer. Natural products have been used for thousands of years by the popular medicine. For instance, one can cite the polysaccharides obtained from the endosperm of leguminous seeds, which are rich in bio-active compounds with potential effects on the health conditions investigated by modern studies. Extracts of Cyamopsis tetragonolobus (GG) and Dimorphandra gardneriana (GFD), through their active compounds, have promising effects against inflammation. The objective of this work was to assess the effects of polysaccharides from GG and GFD on the gastric mucosal defence by using an experimental animal model of gastric lesion induced by 50% ethanol and to assess the possible role played by H2S and NO/KATP pathway. Swiss mice were pre-treated by gavage with saline and polysaccharides GG and GFD at dosages of 10, 30 or 90 mg/kg orally 30 minutes before administration of 50% ethanol (0.5 ml/25g). After 1 hour, the mice were euthanised and their stomach open to measure the lesion area by using computed planimetry. In addition, tissue fragments were removed for microscopic analysis and assessment of parameters of oxidative stress, haemoglobins, nitrite levels and gastric mucus. The other groups of mice were treated with L-NAME (10 mg/kg, i.p.), propargylglycine (50 mg/kg, i.p.), glibenclamide (10 mg/kg, i.p.) or saline. After 30 minutes, the mice were given GG and GFD (30 mg/kg – the best dose, p.o.) and after further 30 minutes they were given 50% ethanol (0.5. ml/25 mg, p.o.). The animals were euthanised after 1 hour and tissue. Fragments removed for microscopic analysis and determination of the dosage of GSH, MDA, MPO and nitrite. GG and GFD have a gastro-protective effect against ethanol-induced lesions, which is observed macroscopically and microscopically. Evidence of these protective effects was based on their capacity to increase the levels of GSH and SOD as well as the secretion of gastric mucus. In addition, GG and GFD were found to decrease the levels of MDA, MPO, nitrite and haemoglobin of the gastric samples from animals submitted to ethanol lesion. It is suggested that gastro-protective effects of GG and GFD are related to the activation of the NO/KATP pathway as the presence of antagonists inhibits such effects.